Hubungan Kelengkapan Informasi Medis Pada RM A-1, RM I-1 dan RM L-8 dengan Keakuratan Pengkodean Diagnosis Appendic Pada Rekam Medis Rawat Inap di RS. TK. III dr. Reksodiwiryo Padang Tahun 2021 - Yulfa Yulia; Oktamianiza Oktamianiza; Kalasta Ayunda Putri; Afridon Afridon; Ayunda Sandony (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
Appendix is included in the 20 most diseases in Kindergarten Hospital. III Dr. Reksowidiryo Padang where there are problems in terms of completeness of medical information on RM A-1, RM I-1 and RM L-8 with the level of accuracy of coding disease diagnosis is still low. This study aims to determine the relationship between completeness of medical information and the accuracy of coding appendic diagnoses based on ICD-10 in medical records at the Kindergarten Hospital. III Dr. Reksowidiryo Padang in 2021. The type of research is correlational, the research is carried out at the Kindergarten Hospital. III Dr. Reksowidiryo Padang, the initial survey was carried out in February with field research on 18 to 22 June 2021, the total population in January-December 2021 was 110 along with a sample of 110 appendic medical record files, the study was conducted by direct observation, data analysis used namely bivariate and univariate. With the results of the study, it was found that the completeness of complete medical information was 42 (38.2%), the completeness of incomplete medical information was 68 (61.8%), the accuracy of the accurate diagnosis code was 45 (40.9%), the accuracy of the code was There were 65 (59.1%) inaccurate diagnoses, with p-value = 0.003 (p0.05), which means that there is a relationship between the completeness of medical information and the accuracy of coding for appendic diagnoses. With the results of the study, it is known that the completeness of medical information and the accuracy of the disease diagnosis code is still not good, the researchers suggest that health workers can fill in each item of the medical record sheet completely and write down the diagnosis code accurately and clearly in order to increase efforts to complete the diagnosis and completeness of the diagnosis medical information.